COMPARATIVE TYPOLOGY OF UZBEK AND RUSSIAN LANGUAGE GRAMMAR - Tevosyan, Gayane (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This paper compares and contrasts the phonology, morphology, syntax, and semantics of the grammars of the Russian and Uzbek languages. We reveal both parallels and discrepancies between these two languages through a methodical analysis of linguistic elements, underscoring the intricate interaction of historical, cultural, and cognitive elements influencing language usage and structure. Consonant and vowel inventories are among the phonological and morphological characteristics that share similarities, but there are also noticeable differences in grammatical categories and syntactic structures, according to our analysis. Furthermore, we investigate how language contact, cultural factors, and cognitive processes shape typological diversity and linguistic variation. We expand on our knowledge of language diversity and universality by using an interdisciplinary approach that incorporates insights from linguistics, anthropology, psychology, and cognitive science.